2019
DOI: 10.1001/jamanetworkopen.2019.3355
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Symptoms of Depression Among Chinese Rural-to-Urban Migrants and Left-Behind Family Members

Abstract: This cross-sectional study analyzes the association of rural-to-urban migration in China with mental health among migrants and their left-behind family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…This study found that the new-generation migrants from rural to urban areas had worse mental health measured by psychological distress and perceived stress scores, which was consistent with evidence from previous studies ( 45 , 46 ). The new-generation migrants tended to be more educated and more likely to develop in cities, but the income inequality caused by the registered permanent residence could lead to great stress and subsequent psychological distress ( 9 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found that the new-generation migrants from rural to urban areas had worse mental health measured by psychological distress and perceived stress scores, which was consistent with evidence from previous studies ( 45 , 46 ). The new-generation migrants tended to be more educated and more likely to develop in cities, but the income inequality caused by the registered permanent residence could lead to great stress and subsequent psychological distress ( 9 , 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the relationship between the rural-to-urban migration path and the mental health of new-generation migrants was mediated by the two dimensions of social integration: life integration and acceptance of the host culture. This study found that the new-generation migrants from rural to urban areas had worse mental health measured by psychological distress and perceived stress scores, which was consistent with evidence from previous studies (45,46). The new-generation migrants tended to be more educated and more likely to develop in cities, but the income inequality caused by the registered permanent residence could lead to great stress and subsequent psychological distress (9,47).…”
Section: Discussionsupporting
confidence: 90%
“…Past research on this study cohort had primarily focused on educational outcomes, namely education rights, dropout rates, and educational consequences [ 38 , 39 ]. There are limited studies that are concerned about this cohort’s mental health [ 40 , 41 , 42 ]. With these findings, we offer recommendations on health and social support required to develop this cohort’s mental health progressively.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rates of anxiety disorders (e.g., Guo et al, 2016), schizophrenia (e.g., Chan et al, 2015), poor mental health status among older population (Wang et al, 2016), and older adults loneliness (e.g., Zhong et al, 2018) were particularly high in modern China. In rural China, prevalence of reproductive depression (Cao et al, 2015), elderly suicide rate (e.g., Zhong et al, 2016), adolescents aggression (Huang et al, 2017), mental health problems among left-behind children (Tang et al, 2018; Wang J. et al, 2019) and spouses (Nikoloski et al, 2019), students anxiety (e.g., Liu H. et al, 2018), self-stigma (Ran et al, 2018), general depression (Qiu et al, 2018), and hopelessness among lower-class rural residents (Zhang et al, 2019) were high. Mental disorders were significantly associated with increased risk of suicide attempt in rural China (e.g., Sun et al, 2015; Liu et al, 2017; Liu B.P.…”
Section: Introductionmentioning
confidence: 99%